Tick Thioester-Containing Proteins and Phagocytosis Do Not Affect Transmission of Borrelia afzelii from the Competent Vector Ixodes ricinus - Urbanová, Veronika (Front Cell Infect Microbiol, 2017)
The present concept of the transmission of Lyme disease from Borrelia-infected Ixodes sp. ticks to the naïve host assumes that a low number of spirochetes that manage to penetrate the midgut epithelium migrate through the hemocoel to the salivary glands and subsequently infect the host with the aid of immunomodulatory compounds present in tick saliva. Therefore, humoral and/or cellular immune reactions within the tick hemocoel may play an important role in tick competence to act as a vector for borreliosis. To test this hypothesis we have examined complement-like reactions in the hemolymph of the hard tick Ixodes ricinus against Borrelia afzelii (the most common vector and causative agent of Lyme disease in Europe). We demonstrate that I. ricinus hemolymph does not exhibit borreliacidal effects comparable to complement-mediated lysis of bovine sera. However, after injection of B. afzelii into the tick hemocoel, the spirochetes were efficiently phagocytosed by tick hemocytes and this cellular defense was completely eliminated by pre-injection of latex beads. As tick thioester-containing proteins (T-TEPs) are components of the tick complement system, we performed RNAi-mediated silencing of all nine genes encoding individual T-TEPs followed by in vitro phagocytosis assays. Silencing of two molecules related to the C3 complement component (IrC3-2 and IrC3-3) significantly suppressed phagocytosis of B. afzelii, while knockdown of IrTep (insect type TEP) led to its stimulation. However, RNAi-mediated silencing of T-TEPs or elimination of phagocytosis by injection of latex beads in B. afzelii-infected I. ricinus nymphs had no obvious impact on the transmission of spirochetes to naïve mice, as determined by B. afzelii infection of murine tissues following tick infestation. This result supports the concept that Borrelia spirochetes are capable of avoiding complement-related reactions within the hemocoel of ticks competent to transmit Lyme disease.